2020
DOI: 10.1116/1.5134764
|View full text |Cite
|
Sign up to set email alerts
|

XPS analysis and electrical conduction mechanisms of atomic layer deposition grown Ta2O5 thin films onto p-Si substrates

Abstract: Metal oxide semiconductor capacitors that incorporate tantalum pentoxide (Ta2O5) thin films as dielectric were fabricated via the atomic layer deposition (ALD) technique and characterized through TEM, XPS, C–V, and I–V measurements. TEM analysis revealed the amorphous phase of Ta2O5 films and the existence of an ultrathin SiOx layer in the Ta2O5/p-Si interface, also evidenced by XPS spectra. XPS analysis verified the stoichiometry of the ALD-deposited Ta2O5 films. Furthermore, XPS results indicate values of 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 62 publications
3
2
0
Order By: Relevance
“…The oxidation rate was estimated to be 2.5 nm min −1 in this study. For ALD in recent studies, the deposition rates of Ta-oxide film were in the range of 0.95-7.5 nm cycle −1 , including the precursor insertion and purge time [25,26]. These synthesis rates are comparable to those in our study, demonstrating that our approach requires a sufficiently process time.…”
Section: Resultssupporting
confidence: 80%
“…The oxidation rate was estimated to be 2.5 nm min −1 in this study. For ALD in recent studies, the deposition rates of Ta-oxide film were in the range of 0.95-7.5 nm cycle −1 , including the precursor insertion and purge time [25,26]. These synthesis rates are comparable to those in our study, demonstrating that our approach requires a sufficiently process time.…”
Section: Resultssupporting
confidence: 80%
“…In Figure 2a, the spin-orbit splitting of Zr 3d is equal to 2.4 eV, and the peak differences in binding energy confirm this [31]. Similarly, in Figure 2b, the response has been fitted to detectable compounds, while the spin-orbit splitting of Ta 4f is 1.8 eV [32]. The binding energy peak at 24.39 eV corresponds to TaON, thus verifying the presence of the TaON interfacial layer in the XPS analysis [33].…”
Section: Resultssupporting
confidence: 52%
“…Two ultra-thin ZnO films of 0.6 and 1.0 nm were also prepared using four and six cycles respectively. The thickness of similar, up to 10 nm, films has been investigated by our team previously [29][30][31] and it was shown that the nominal growth rates are in agreement with the calculated ones. Also, films with thickness of at least 20 nm of Al 2 O 3 , ZrO 2 , HfO 2 and Ta 2 O 5 were prepared and will be noted as reference samples.…”
Section: Sample Preparationsupporting
confidence: 62%
“…Although the Kraut method is usually applied for conductive samples, it has also been used for wide bandgap oxides [6,[46][47][48][49]. A comparison of the Kraut method with the results obtained from electrical measurements for the determination of the band offsets of the Ta 2 O 5 /Si interface, was recently published by our group, showing that the two methods compare well to each other [29]. The Kraut method can be summarized in equations ( 1)-( 3), where 'f', 's', 'ref' and 'int' refer to 'film', 'substrate', 'reference' and 'interface', respectively:…”
Section: Band Offsetsmentioning
confidence: 94%